1997
DOI: 10.1002/(sici)1098-2329(199711)16:4<323::aid-adv6>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Reactive blending of ethylene-methylacrylate copolymer and poly-dimethyl siloxane rubber: kinetics studies from infrared spectroscopy

Abstract: Kinetics of reaction between ethylene‐methylacrylate copolymer and poly‐dimethyl siloxane rubber during melt processing has been studied from the infrared spectrophotometric data. The kinetic pattern confirms first order kinetics and the activation energy of the reaction was found to be 17 kJ/mole. © 1997 John Wiley & Sons Inc. Adv Polym Techn 16: 323–329, 1997

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…The fly in the ointment is that polyester plasticizers are still deficient in their processing capacity and low temperature resistance. Silicone has a SiOSi bond and has excellent characteristics such as high and low temperature resistance, oxidation stability, flame resistance, hydrophobicity, nontoxicity and tastelessness, and physiological inertness . To improve the processing capacity and low temperature resistance of polyester, we tried to use organosilicon monomers 1,1,3,3‐tetramethyldisiloxane (TD), which contain SiOSi bonds to synthesize a new type of plasticizer by hydrosilicon‐hydrogenation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The fly in the ointment is that polyester plasticizers are still deficient in their processing capacity and low temperature resistance. Silicone has a SiOSi bond and has excellent characteristics such as high and low temperature resistance, oxidation stability, flame resistance, hydrophobicity, nontoxicity and tastelessness, and physiological inertness . To improve the processing capacity and low temperature resistance of polyester, we tried to use organosilicon monomers 1,1,3,3‐tetramethyldisiloxane (TD), which contain SiOSi bonds to synthesize a new type of plasticizer by hydrosilicon‐hydrogenation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(acrylate/silicone) hybrid polymers and adhesives have been discussed before [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. However, none of these works focused on their use for adhesion to substrates with low surface energy such as PE, iPP, or PTFE.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, different methods have been employed for improving the interfacial adhesion of the phases in a blend, such as functionalization of the components before blending [12][13][14][15][16] , addition of compatibilizer during mixing [17][18][19] , and in situ reactive melt mixing [20][21][22][23] . Nando and co-workers investigated the compatibilising effects of four ethylene copolymers [EMA, EVA, EAA and a zinc-salt-based ionomer (Lotek 4200)] on an LDPE/PDMS blend [24][25][26][27] . However, the results showed that of the compatibilizer lowered the thermal stability of the blend because of its own inherent low thermal stability.…”
Section: Introductionmentioning
confidence: 99%